An information technology in Excel when executing an individual calculation task within the course Mathematical statistics - Litvinov, A. (Problems of Engineer-Pedagogical Education, 2019)
The article presents the results of the process of elaborating an information technology which automatizes the processing of sequences of statistical data (samples) when executing an individually calculated task (ICT) in Microsoft Office Excel. An ICT plays a special role within the course “Mathematical Statistics”, and allows using the acquired theoretical knowledge comprehensively during a single process. Solving problems of mathematical statistics in the context of educational programs for engineering specialties requires a significant amount of computation, associated with a significant number of characteristics, complex algorithms for their calculation and graphical interpretation of the results of solutions. Traditionally, while working on an ICT, students are offered a set of statistical data (sample) with an unknown distribution law. From this sample, it is necessary to determine the estimate for the mathematical expectation of the sample data, the estimate for the dispersion and standard deviation, structural averages, build a histogram of the distribution, suggest a null hypothesis about the type of the distribution and use the χ2 criterion to accept or reject the hypothesis. In the manual mode, these calculations are rather time-consuming and monotonous, which requires the use of computer equipment when performing them. It should be noted that the use of computer technology in the educational literature with respect to the discipline “Mathematical Statistics” is given very little attention. Within the course “Computer Science”, only certain functions of calculating statistical characteristics are considered, which complicates the use of mathematical statistics in the educational process. Excel is one of the most available applications for students. Therefore, one of the main goals of this article is to develop an information technology in Excel for consistent calculation of sample characteristics. The proposed technology consists of a number of stages, for the implementation of which either built-in Excel functions or programmable expressions in spreadsheet cells are used. Particular attention is paid to building a distribution histogram, suggesting a hypothesis about the type of the distribution, and verifying statistically this hypothesis. The effectiveness of the technology is proved by the example provided.